Susanna Mancini The Decriminalization of Abortion in Colombia: The Role of Social Movements and Strategic litigation (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This article analyzes the progressive decriminalization of abortion in Colombia. It focuses on the case-law of the Colombian Constitutional Court, and in particular on its reliance on international human rights law and on dignity, as well as on proportionality as a judicial standard to strike down provisions criminalizing abortion. Moreover, the article emphasizes the role of transnational social movements in shaping the Court’s case-law and in changing social perceptions on abortion. It argues that the Colombian case showcases how the Court’s approach may ultimately diffuse tension and protect its own legitimacy.
Keywords: Colombia; abortion; constitutional court; mobilization; vulnerability; intersectional equality; conscientious objection; dignity